Comparison Of The Effect Of Acid Type Of Cuko Pempek On The Surface Hardness Of Mycrohybrid And Nanohybrid Composite Resin - Aisyah Azzahra; Maya Hudiyati; Rinda Yuliati (Sriwijaya Journal of Dentistry, 2020)
Abstract often used nowadays because of the combination of filler with good aesthetic and mechanical strength. Various factors in the oral cavity such as acid solution can affect the surface hardness of composite resin. Cuko pempek is an additional sauce that served which has acidic pH. This study aimed to compare the effect of acid type of cuko pempekhardness of microhybrid and nanohybrid composite. Materials and Methods:Thirty-six samples of microhybrid (n=18) and nanohybrid composite (n=18) with 5 mm in diameter and 2 mm in thickness were immersed in three different solutions: artificial saliva (control), cuko pempek using vinegar, and cuko pempekSurface hardness was measured before and after immersion using Vickers Hardness Tester. Resultsshowed a significant difference on the surface hardness of composite resin before and after ardness of microhybrid and nanohybrid composites after (p<0,0167) showed statistically significant differences, while there were no cuko pempek using vinegar and tamarind (p>0,0167). This study alsothat there were significant differences on the surface hardness of microhybrid and nanohybrid composite after cuko pempek using vinegar, and cuko pempek using tamarind (p<0,05). face hardness of nanohybrid composite was lower than microhybrid composite after using vinegar and tamarind. composite resin, surface hardness.